PROGRESIFITAS FORMULASI HUKUM EKONOMI SYARIAH DI INDONESIA - Yasin, Mohamad Nur (Fakultas Syariah, 2014)
The chronological journey of sharia economic law begin from a level of normative-indicative consisting Quranic verses until to be indicate that there is progressive massively. Each phase appearing indicate the axistance of intensive dialog of civilization and cultur between the law of syariah economic and the law of conventional economic. The intensive-interactive dialog appears a product of new thought reconstructively basing logic of discover (logika temuan baru) and not logic of repetition (logika mengulang-ngulang). In the middle of interconnection of economic, social, politic, and law, the writerÂ formulates four conceptual phases pharadigmatically representing long journey of syariah economic law begin from syariah era, fiqh era, qÃ¢nÃ»n era, and qadla era.